1985
DOI: 10.1007/bf01403756
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection in the presence of horizontal impermeable surfaces in saturated porous media with variable permeability

Abstract: Abstract. Boundary layer approximation is applied for mixed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…In some applications, such as fixed-bed catalytic reactors, packed bed heat exchangers and drying, the porosity is not uniform but has a maximum value at the wall and a minimum value away from the wall. This wall-channeling phenomenon has been reported by a number of investigators such as Vafai [6], Chandrasekhara et al [7], Chandrasekhara [8], and Hong et al [9] for forced, natural, and mixed convection boundary layer flows adjacent to a horizontal and vertical surfaces. It is shown that the variable porosity effect increases the temperature gradient adjacent to the wall resulting in the enhancement of the surface heat flux.…”
Section: Introductionsupporting
confidence: 60%
“…In some applications, such as fixed-bed catalytic reactors, packed bed heat exchangers and drying, the porosity is not uniform but has a maximum value at the wall and a minimum value away from the wall. This wall-channeling phenomenon has been reported by a number of investigators such as Vafai [6], Chandrasekhara et al [7], Chandrasekhara [8], and Hong et al [9] for forced, natural, and mixed convection boundary layer flows adjacent to a horizontal and vertical surfaces. It is shown that the variable porosity effect increases the temperature gradient adjacent to the wall resulting in the enhancement of the surface heat flux.…”
Section: Introductionsupporting
confidence: 60%
“…In some applications, such as fixed-bed catalytic reactors, packed bed heat exchangers, and drying, the porosity is not uniform but has a maximum value at the wall and a minimum value away from the wall. This wall-channeling phenomenon has been reported by a number of investigators, such as Vafai [6], Chandrasekhara [7], Hassanien and Elaiw [8]. It is shown that the variable porosity effect increases the temperature gradient adjacent to the wall, resulting in the enhancement of the surface heat flux.…”
Section: Introductionsupporting
confidence: 57%
“…The effect of the non-uniform temperature profile on the wall is also studied, and corresponds to variations of the parameter m. Moreover, the effect of the inclination angle φ is studied. For the purpose of numerical integration we have assumed d = 1.5, d * = 3, ε ∞ = 0.4, σ = 2 (Chandrasekhara [7]).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It is found from the Table 1 that the thickness A of the second boundary layer is always greater than the thickness of the first boundary layer 6 since ~ is greater than unity for all values of B. The values of B, the dimensionless porous parameter are kept low since the permeability at the wall increases due to the packing of the particles (see Chandrasekhara and Votmeyer [6], Benenati and Brosilow [7] Chandrasekhara et al [8], Chandrasekhara [9] and Chandrasekhara and Namboodiri [10]. However, it is observed from the results that the value of 4 does not …”
Section: --2at +A~o~176 B~-o~mentioning
confidence: 97%